Adaptation and validation of the Cyprus version of the practice environment scale of the nursing work index: a methodological study - Efstathiou, Georgios; Andreou, Christos; Tsangari, Haritini; Dimitriadou, Maria; Papastavrou, Evridiki (My University, 2018)
Objective: The purpose of this study was to adapt and validate the Revised Practice Environment Scale of the Nursing Work Index, to be utilized among the Cyprus nurses' population. Validated research scales are valuable tools in the hands of researchers in their attempt to recommend alterations within health care systems, especially during reform periods. Results: Internal consistency reliability of the scale was satisfactory (alpha = 0.94). Exploratory factor analysis produced a five-factor structure solution. Experts in the field provided further guidance. The findings demonstrated that the Cyprus version of the Revised Practice Environment Scale of the Nursing Work Index is a reliable and valid research instrument, however differences with previous studies on the factor structure were observed, mainly due to cultural reasons. As a valid and reliable scale, it can capture the views of nurses concerning their work environment. The Cyprus version of the Revised Practice Environment Scale of the Nursing Work Index can be used by nurse managers and policy makers to introduce changes that may improve the quality of nursing care provided and enhance the patients' satisfaction from the health system as a whole.
Keywords: Adaptation; Cyprus; Nurses; RN4CAST; Validation; Working environment